IDENTIFICATION OF POTENTIAL HAZARDS AND RISK ASSESSMENT OF THE CATTLE SLAUGHTERING AT THE SLAUGHTERHOUSE - Zelia Danila Amaral Guterres; I Wayan Suardana; I Ketut Suada (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
The beef is a food product with a high nutritional content. However, not all beef products are of good quality. In the process of slaughtering beef, there is a high chance of carcass contamination. Biological, physical and chemical interventions can cause the number of microbes in the carcass to decrease significantly. This study used direct observation method to the location and informant interviews to obtain data, the study was conducted in 15 observations. Furthermore, the data was analyzed using Failure Modes and Effect Analysis (FMEA) to determine the potential hazards and risk assessment. The results of the research in the Cattle Slaughtering unit at the Pesanggaran Slaughterhouse showed that of the 11 cattle slaughtering activities, 7 activities need to be improved, and 4 activities have been carried out properly and correctly according to the standard. The 7 activities that need to be improved are, antemortem examination stage has a RAC score of 9, cattle put in restraining box has a RAC score of 4, slaughter has a RAC score of 4, head separation has a RAC score of 6, skinning and offal removal has a RAC score of 3, postmortem examination has a RAC score of 9, and transportation has a RAC score of 3. There are 4 activities that have been carried out properly and correctly, which are at the stage of receiving cattle, resting cattle, cutting metacarpals and metatarsals, and separating carcasses. The conclusion of this study is that all potential hazards are categorized as unacceptable and undesirable. The purpose of this study is to identify potential hazards and risk assessment in the process of slaughtering cattle in the Pesanggaran slaughterhouse.